SARS-CoV-2 Antibodies in Unvaccinated Older Population and its Relationship with Hematological Parameters - Yousafzai, Yasar Mehmood; Zahir Shah; Khan, Muhammad Ihtesham; Muhammad Arif; Nazish Farooq (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: The objective of this study was to determine the prevalence of SARS-CoV-2 (Immunoglobulin-G) antibodies in unvaccinated older populations and their relationship with hematological parameters. METHODOLOGY: The study was conducted from March to August 2022. Two-hundred forty six healthy unvaccinated individuals aged 60 and above were included by random sampling. Blood specimens were obtained to determine antibodies using the ECLIA technique. Data was analyzed with SPSS version 26. RESULTS: The study showed that 170 (69.11%) participants were male, while 76 (30.89%) were female. Mean age of study sample was 67±6.9 (range:60-100) years. Participants were categorized into two age groups: Group I (60-69 years) had 163 (66.30%) participants, and Group II (70-100 years) had 83 (33.70%). IgG antibodies were positive in 225 (91.46%) participants and negative in 21 (8.54%). When considering gender, IgG was positive in 155/170 (91.17%) males and 70/76 (92.11%) females and negative in 15/170 (8.82%) males and 6/76 (7.89%) females. Regarding age groups, IgG was positive in 154/163 (94.48%) in Group I and 71/83 (85.54%) in Group II. No significant relationship was found between IgG and hematological parameters. CONCLUSION: Our study showed a 91% prevalence of IgG antibodies in the older population. The seroprevalence of antibodies against SARS-CoV-2 in the older population has increased. However, they still need vaccination so that the risk of getting an infection can be minimized.